Method for manufacturing plastic component having fine concavo-convex structure on surface
A two-step reactive ion etching process with controlled gas atmospheres and plasma treatment effectively generates a fine concave-convex structure on plastic components, addressing precision and waterproofing challenges for optical elements.
Patent Information
- Application Number
- CN201980095688.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-06-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2039-06-11
AI Technical Summary
Existing methods struggle to precisely transfer a fine concave-convex structure with desired pitch and depth onto plastic components, particularly for optical elements, using reactive ion etching processes.
A method involving two-step reactive ion etching using different gas atmospheres to control the pitch and depth of the concave-convex structure, followed by plasma treatment to bond fluorine radicals for waterproofing.
Achieves a fine concave-convex structure on plastic components with optimal pitch and depth for anti-reflection, enhancing light transmission and reducing reflection, while also providing waterproofing.
Smart Images

Figure CN113727827B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a plastic component having a fine concave-convex structure on the surface. The plastic component includes an optical component made of plastic. The optical component includes a lens, a diffraction grating, a prism, a microlens array, a diffusion plate, and a protective window. Background Art
[0002] An anti-reflection structure formed by a fine concave-convex structure arranged at a small pitch (period) of the wavelength of light or less is used in an optical element. As a method for manufacturing a molding die for such a fine concave-convex structure, a method of etching or electroforming by patterning a resist using an interference exposure device or an electron beam drawing device is known. However, it is difficult to form a fine concave-convex structure on a large-area flat or curved surface using these methods.
[0003] Therefore, a method for manufacturing a molding mold with a fine concave-convex structure by a reactive ion etching process without patterning has been developed (for example, Patent Document 1). According to this method, a molding mold with a fine concave-convex structure on a large flat or curved surface can be manufactured without patterning. However, when a plastic component is manufactured using a molding mold manufactured using the above method, it is not easy to transfer the fine concave-convex structure of the molding mold to the plastic material with high precision.
[0004] In addition, a method for directly generating a fine concave-convex structure on the surface of a plastic component such as a lens by a reactive ion etching process has been developed (e.g., Patent Document 2). However, a method for directly generating a fine concave-convex structure with a pitch and depth suitable for preventing reflection of light in the visible light region on the surface of a plastic component by a reactive ion etching process has not yet been established. Specifically, in the existing methods, it is difficult to make the pitch and depth of the fine concave-convex structure generated on the surface of the plastic component become the desired values.
[0005] Thus, a manufacturing method for a plastic component having a fine concavo-convex structure on its surface, which can directly generate a fine concavo-convex structure with a desired pitch and a desired depth on the surface of the plastic component by a reactive ion etching process, has not yet been developed.
[0006] Therefore, there is a need for a manufacturing method for a plastic component having a fine concavo-convex structure on its surface, which method can directly generate a fine concavo-convex structure with a desired pitch and a desired depth on the surface of the plastic component by a reactive ion etching process.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: WO2014 / 076983A1
[0010] Patent document 2: DE10241708A1 Summary of the invention
[0011] Problems to be solved by the invention
[0012] The technical problem of the present invention is to provide a manufacturing method, which is a manufacturing method of a plastic component having a fine concavo-convex structure on the surface, and the method can directly generate a fine concavo-convex structure with a desired pitch and a desired depth on the surface of the plastic component through a reactive ion etching process.
[0013] Means for solving problems
[0014] The method for manufacturing a plastic element having a fine concave-convex structure on the surface of the present invention comprises the following steps: a first step of generating a fine concave-convex structure having an average pitch of a specific value in the range of 0.05 microns to 1 micron on the surface of the plastic element by reactive ion etching in a first gas atmosphere; and a second step of making the average depth of the structure a specific value in the range of 0.15 microns to 1.5 microns in a second gas atmosphere having a lower reactivity to the plastic element than the reactivity of the first gas to the plastic element.
[0015] According to the present invention, in the first step, the fine concave-convex structure with an average pitch of a desired value can be generated, and then in the second step, the average depth of the fine concave-convex structure can be made to a desired value while approximately maintaining the specific value of the average pitch by reactive ion etching in a second gas atmosphere whose reactivity to the plastic element is lower than that of the first gas to the plastic element, thereby directly generating a fine concave-convex structure with a desired pitch and a desired depth on the surface of the plastic element.
[0016] In the method for manufacturing a plastic element having a fine concavo-convex structure on the surface of the first embodiment of the present invention, the first gas is sulfur hexafluoride (SF6), a mixture of sulfur hexafluoride and at least one of oxygen (O2) or argon (Ar), or oxygen.
[0017] In the method for manufacturing a plastic element having a fine concave-convex structure on the surface of the second embodiment of the present invention, the gas used in the second step is trifluoromethane (CHF3), a mixture of trifluoromethane and at least one of oxygen or argon, carbon tetrafluoride (CF4), a mixture of carbon tetrafluoride and at least one of oxygen or argon.
[0018] The method for manufacturing a plastic element having a fine concavo-convex structure on the surface according to the third embodiment of the present invention further comprises a third step of bonding fluorine radicals to the surface of the fine concavo-convex structure by plasma treatment in a third gas atmosphere without causing ion etching.
[0019] According to this embodiment, the plastic element having a fine concavo-convex structure can be waterproofed by plasma treatment. The third step can also be performed using a reactive ion etching device for performing the first and second steps by changing the connection between the high frequency power supply device and the electrode.
[0020] In the method for producing a plastic element having a fine concavo-convex structure on the surface according to a fourth embodiment of the present invention, the third gas is trifluoromethane, carbon tetrafluoride or sulfur hexafluoride.
[0021] In the method for producing a plastic element having a fine concavo-convex structure on the surface according to the fifth embodiment of the present invention, the plastic element is an optical element.
[0022] In the method for producing a plastic element having a fine concavo-convex structure on the surface according to a sixth embodiment of the present invention, the fine concavo-convex structure is an antireflection fine concavo-convex structure.
[0023] According to this embodiment, it is possible to manufacture a plastic element having a fine concavo-convex structure having an appropriate average pitch and average depth according to the wavelength of light whose reflection is to be prevented. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 1 is a diagram showing a configuration of a reactive ion etching (RIE) apparatus 100A used in an etching method according to an embodiment of the present invention.
[0025] Figure 2 This is a scanning electron microscope (SEM) image of a fine concavo-convex structure obtained by etching under condition 1.
[0026] Figure 3 This is a SEM image of the fine concavo-convex structure obtained by etching under condition 2.
[0027] Figure 4 This is a flowchart for explaining an etching method according to one embodiment of the present invention.
[0028] Figure 5A It is a diagram for explaining an etching method according to one embodiment of the present invention.
[0029] Figure 5B It is a diagram for explaining an etching method according to one embodiment of the present invention.
[0030] Figure 5C It is a diagram for explaining an etching method according to one embodiment of the present invention.
[0031] Figure 6 This is a flowchart for explaining the method of determining etching conditions in the first step.
[0032] Figure 7 This is a flowchart for explaining the method of determining etching conditions in the second step.
[0033] Figure 8 This is a flowchart for explaining a method for determining target values of the average pitch and average depth of a fine concavo-convex structure.
[0034] Fig. 9 This is a SEM image of the antireflection fine concavo-convex structure for visible light generated by the above method.
[0035] Fig.10 It is a graph showing the relationship between wavelength and reflectivity.
[0036] Fig.11 It is a graph showing the relationship between wavelength and transmittance.
[0037] Fig.12 This is a SEM image of the surface of a plastic component after etching using only trifluoromethane (CHF3).
[0038] Fig.13 This is a SEM image of the surface of a plastic component after etching using only sulfur hexafluoride (SF6).
[0039] Fig.14 This is a SEM image of the surface of a plastic component after etching using only oxygen.
[0040] Fig.15 It is a graph showing the relationship between wavelength and transmittance.
[0041] Fig.16 This is an SEM image of the antireflection fine concavo-convex structure for visible light generated by the method shown in Table 4.
[0042] Fig.17 It is a graph showing the relationship between wavelength and reflectivity.
[0043] Fig.18 It is a graph showing the relationship between wavelength and transmittance.
[0044] Fig.19 This is a diagram showing a configuration of a water repellent treatment apparatus 100B used in water repellent treatment according to an embodiment of the present invention.
[0045] Fig. 20This is a photo of water droplets formed on the surface of a plastic component with a fine concavo-convex structure that has not been treated for water repellency.
[0046] Fig.21 This is a photograph of water drops formed on the surface of a plastic element having a fine concavo-convex structure that was subjected to water repellent treatment according to condition 1 of Table 6.
[0047] Fig. 22 This is a photograph of water drops formed on the surface of a plastic element having a fine concavo-convex structure that was subjected to water repellent treatment according to condition 2 of Table 6. DETAILED DESCRIPTION
[0048] Figure 1 1 is a diagram showing the structure of a reactive ion etching (RIE) device 100A used in an etching method according to an embodiment of the present invention. The reactive ion etching device 100A has a reaction chamber 101. Gas is supplied to the vacuum-exhausted reaction chamber 101 from a gas supply port 111. The amount of gas supplied can be adjusted. In addition, a gas exhaust port 113 is provided in the reaction chamber 101, and a valve not shown is installed in the gas exhaust port 113. By operating the valve, the gas pressure in the reaction chamber 101 can be set to a desired pressure value. The reaction chamber 101 is provided with a grounded upper electrode 103 and a lower electrode 105 connected to a high-frequency power supply 107, and a high-frequency voltage can be applied between the two electrodes by the high-frequency power supply 107 to generate plasma. A plastic element 200 is arranged on the lower electrode 105. As an example, the plastic element 200 is a lens made of plastic. The lower electrode 105 can be cooled to a desired temperature by a cooling device 109. The cooling device 109 is a device that uses a water-cooled cooler for cooling, for example. The lower electrode 105 is cooled in order to control the etching reaction by making the temperature of the plastic element 200 a desired temperature.
[0049] use Figure 1 The reactive ion etching apparatus described in the description is a capacitively coupled ion etching apparatus, but another type of ion etching apparatus, for example, an inductively coupled ion etching apparatus may be used.
[0050] When a high-frequency voltage is applied to the lower electrode 105 on which the plastic element 200 is disposed, ions or radicals in the plasma are accelerated toward the plastic element 200 and collide with the plastic element 200. At this time, sputtering based on ions and a chemical reaction of the etching gas occur simultaneously, and etching is performed. The plastic of the plastic element 200 is formed by a plurality of molecular chains, and dense and sparse molecular chains are randomly present on the surface of the plastic element 200. Since dense molecular chain portions are not easily etched and sparse molecular chain portions are easily etched, a fine concavo-convex structure is generated on the surface of the plastic element 200 by etching.
[0051] Table 1 is a table showing etching conditions and the average pitch and average depth of the fine concavo-convex structure produced by etching under the etching conditions. The plastic component 200 is made of polycarbonate. In Table 1 and other tables, RF power is the power supplied by the high frequency power supply 107, the processing temperature is the temperature controlled by the cooling device 109, and the processing time is the time for processing while supplying power.
[0052] [Table 1]
[0053]
[0054] Condition 1 and Condition 2 differ only in processing time. Generally, the longer the processing time (etching time), the greater the average spacing and average depth of the fine concave-convex structure. Therefore, by changing the processing time, the average spacing and average depth of the fine concave-convex structure can be changed in the same way. According to Table 1, the average spacing and average depth of the fine concave-convex structure obtained by etching under Condition 2 with a long processing time are greater than the average spacing and average depth of the fine concave-convex structure obtained by etching under Condition 1 with a short processing time.
[0055] On the other hand, since the anti-reflection function of the fine concave-convex structure is determined by the average spacing and the average depth, in order to obtain the desired anti-reflection function, it is necessary to make the average spacing and the average depth respectively the desired values. However, it is difficult to make the average spacing and the average depth respectively the desired values by only processing time. For example, as described below, the depth of the fine concave-convex structure obtained by etching under condition 1 is too small to obtain the desired anti-reflection function for visible light, and the depth of the fine concave-convex structure obtained by etching under condition 2 is appropriate for obtaining the desired anti-reflection function for visible light, but the average spacing is too large, which will produce white turbidity due to the reflection of various wavelengths of visible light.
[0056] The average pitch and average depth can also be changed by using the power supplied by the high-frequency power supply 107. However, in this case, the average pitch and average depth also increase with the magnitude of the power, so it is difficult to make the average pitch and average depth respectively the desired values.
[0057] Figure 2 This is a scanning electron microscope (SEM) image of the fine concavo-convex structure obtained by etching under condition 1.
[0058] Figure 3 This is a SEM image of the fine concavo-convex structure obtained by etching under condition 2.
[0059] The inventors observed the formation process of a fine concave-convex structure based on etching, and found that a fine concave-convex structure with a small pitch and a small depth is formed in the early stage, and the pitch and depth increase with the passage of time in the subsequent stage. Therefore, the inventors tried to divide the etching into an early stage (i.e., step 1) and a subsequent stage (i.e., step 2), and suppress the etching in the second step. As a result, the inventors obtained the following new discovery: if an atmospheric gas with lower reactivity than the atmospheric gas in the first step is used in the second step, it is possible to increase the depth without increasing the pitch in the second step. That is, it was found that by dividing the etching into the first step and the second step using an atmospheric gas with lower reactivity than the atmospheric gas in the first step, the pitch and depth of the fine concave-convex structure can be made to the desired values, respectively.
[0060] Figure 4 This is a flowchart for explaining an etching method according to one embodiment of the present invention.
[0061] Figure 5A - Figure 5C It is a diagram for explaining an etching method according to one embodiment of the present invention.
[0062] Figure 4 In step S1010 , a fine concavo-convex structure having an average pitch of a specific value is generated on the surface of the plastic component 200 by reactive ion etching (RIE) in a first gas atmosphere. Figure 5A is a diagram showing the plastic component 200 before the step S1010 is implemented, Figure 5B is a diagram showing the plastic component 200 after step S1010 is performed.
[0063] Figure 4 In step S1020, reactive ion etching (RIE) is performed in a second gas atmosphere having a lower reactivity than the first gas, while maintaining an average pitch of the fine concavo-convex structure and making the average depth of the fine concavo-convex structure a desired value. Figure 5C is a diagram showing the plastic component 200 after step S1020 is performed.
[0064] Regarding the target value P of the average pitch of the fine concave-convex structure for anti-reflection, assuming that the wavelength of light is λ, the refractive index of the plastic element is n, and the incident angle of light on the surface of the plastic element is θ, it needs to be set to satisfy the following formula.
[0065] [Number 1]
[0066]
[0067] Assuming the wavelength of light is λ = 0.4μm, the refractive index of the plastic component is n = 1.5, and the incident angle of light on the surface of the plastic component is θ = 30°, the target value P needs to be less than 0.2μm. Generally, the target value of the average depth of the fine concave-convex structure for anti-reflection needs to be at least 0.35 times the wavelength λ of the light. For the maximum wavelength of visible light of 0.7μm, the average depth is about 0.25μm or more.
[0068] Figure 6 This is a flowchart for explaining the method of determining etching conditions in the first step.
[0069] Figure 6 In step S2010, reactive ion etching (RIE) is performed in a first gas atmosphere under specific etching conditions.
[0070] Figure 6 In step S2020, the generated fine concavoconvex structure is observed to determine whether the average spacing is the desired value, that is, the target value. If the average spacing is the desired value, the process ends. If the average spacing is not the desired value, the process proceeds to step S2030.
[0071] exist Figure 6 In step S2030, the power or time setting value is changed in such a way that the average pitch of the fine concave-convex structure becomes a desired value. To increase the average pitch, the power or time setting value is increased; to decrease the average pitch, the power or time setting value is decreased. After step S2030 is completed, the process returns to step S2010.
[0072] Figure 7 2 is a flowchart illustrating a method for determining etching conditions in step 2. Figure 6 After the first step is performed according to the etching conditions determined by the method shown in the flowchart, Figure 7 The etching conditions of step 2 are determined by the method shown in the flowchart.
[0073] exist Figure 7 In step S3010, reactive ion etching (RIE) is performed in a second gas atmosphere under prescribed etching conditions.
[0074] exist Figure 7 In step S3020, the generated fine concavo-convex structure is observed to determine whether the average depth is the desired value, that is, the target value. If the average depth is the desired value, the process ends. If the average depth is not the desired value, the process proceeds to step S3030.
[0075] exist Figure 7In step S3030, the power or time setting value is changed in such a way that the average depth of the fine concavo-convex structure becomes the desired value. To increase the average depth, the power or time setting value is increased; to decrease the average depth, the power or time setting value is decreased. After step S3030 is completed, the process returns to step S3010.
[0076] Figure 8 This is a flowchart for explaining a method for adjusting target values of the average pitch and average depth of a fine concavo-convex structure.
[0077] Figure 8 In step S4010, by Figure 6 and Figure 7 The method shown in the flowchart generates a fine concavo-convex structure with a desired average pitch and a desired average depth.
[0078] Figure 8 In step S4020, the reflectivity and transmittance of the plastic component are evaluated.
[0079] Figure 8 In step S4030, it is determined whether the reflectivity and transmittance of the plastic component are satisfactory. If satisfactory, the process ends. If not satisfactory, the process proceeds to step S4040.
[0080] exist Figure 8 In step S4040, the target value of at least one of the average spacing and the average depth is changed. After step S4040 is completed, the process returns to step S4010.
[0081] Table 2 is a table showing etching conditions of an etching method according to one embodiment of the present invention and average pitch and average depth of a fine concavo-convex structure generated by the etching method. The plastic component 200 is made of polycarbonate.
[0082] [Table 2]
[0083]
[0084] The first gas as the atmosphere gas in the first step is a mixed gas of oxygen and sulfur hexafluoride (SF6). The second gas as the atmosphere gas in the second step is a mixed gas of oxygen and trifluoromethane (CHF3). The reactivity of the second gas to plastic components is lower than the reactivity of the first gas to plastic components. After the first step, the average spacing is 0.06μm and the average depth is 0.1μm. In the second step, the average depth increases from 0.1μm to 0.3μm, but the average spacing is maintained at 0.06μm. In this way, a fine concave-convex structure with an average spacing and an average depth suitable for anti-reflection of visible light is obtained.
[0085] Fig. 9This is a SEM image of the antireflection fine concavo-convex structure for visible light produced by the method shown in Table 2. As shown in Table 2, the average pitch is 0.06 μm and the average depth is 0.3 μm.
[0086] Fig.10 It is a graph showing the relationship between wavelength and reflectivity. Fig.10 The horizontal axis represents the wavelength, Fig.10 The vertical axis represents reflectivity. The solid line represents the reflectivity of a plastic element having a fine concave-convex structure obtained by the method of the present invention shown in Table 2. The dotted line marked as "Existing method" represents the reflectivity of a plastic element having a fine concave-convex structure obtained by the method shown in Condition 2 of Table 1. The dotted line marked as "Unprocessed" represents the reflectivity of a plastic element without a fine concave-convex structure.
[0087] Fig.11 It is a graph showing the relationship between wavelength and transmittance. Fig.11 The horizontal axis represents the wavelength, Fig.11 The vertical axis represents transmittance. The solid line represents the transmittance of a plastic element having a fine concave-convex structure obtained by the method of the present invention shown in Table 2. The dotted line marked as "Existing method" represents the transmittance of a plastic element having a fine concave-convex structure obtained by the method shown in Condition 2 of Table 1. The dotted line marked as "Unprocessed" represents the transmittance of a plastic element that has not been etched and does not have a fine concave-convex structure.
[0088] Implementation Fig.10 The reflectivity is shown in the Fig.11 The plastic element for which the transmittance is measured is a plate-like element having a thickness of 5 mm.
[0089] according to Fig.10 The reflectivity of the plastic element having a fine concave-convex structure obtained by the method of the present invention is less than 1% in the visible light range of 400 nanometers to 700 nanometers, which is lower than the reflectivity of the plastic element having a fine concave-convex structure obtained by the method shown in Condition 2 of Table 1.
[0090] according to Fig.11 The transmittance of the plastic element having the fine concavo-convex structure obtained by the method of the present invention is 90% or more in the visible light range of 400 nm to 700 nm, which is higher than the transmittance of the plastic element having the fine concavo-convex structure obtained by the method shown in Condition 2 of Table 1. In addition, the transmittance of the plastic element having the fine concavo-convex structure obtained by the method of the present invention is about 5% higher in the visible light range of 400 nm to 700 nm than the transmittance of the plastic element without the fine concavo-convex structure.
[0091] Next, etching in a single gas atmosphere will be described.
[0092] Table 3 is a table showing etching conditions of etching in a single gas atmosphere and the average pitch and average depth of the fine concavo-convex structure produced by the etching. The plastic component 200 is made of polycarbonate.
[0093] [Table 3]
[0094]
[0095] Fig.12 : is a SEM image of the surface of the plastic component after being treated in a gas atmosphere of only trifluoromethane (CHF3).
[0096] Fig.13 is a SEM image of the surface of a plastic component after being treated with only a sulfur hexafluoride (SF6) gas atmosphere.
[0097] Fig.14 is a SEM image of the surface of a plastic component after being treated in a gas atmosphere containing only oxygen (O 2 ).
[0098] The average spacing of the fine concavo-convex structure generated after the treatment with sulfur hexafluoride gas atmosphere alone is larger than the average spacing of the fine concavo-convex structure generated after the treatment with trifluoromethane gas atmosphere alone, and the average depth of the fine concavo-convex structure generated after the treatment with sulfur hexafluoride gas atmosphere alone is larger than the average depth of the fine concavo-convex structure generated after the treatment with trifluoromethane gas atmosphere alone. Therefore, it can be seen that the reactivity of sulfur hexafluoride to plastic components made of polycarbonate is higher than the reactivity of trifluoromethane to plastic components made of polycarbonate.
[0099] according to Fig.14 , no fine concavo-convex structure was generated on the surface of the plastic element after treatment in the gas atmosphere containing only oxygen.
[0100] Fig.15 It is a graph showing the relationship between wavelength and transmittance. Fig.15 The horizontal axis represents the wavelength, Fig.15 The vertical axis represents transmittance. The thick solid line represents the transmittance of the plastic element having a fine concave-convex structure obtained by the method of the present invention shown in Table 2. The dotted line represents the transmittance of the plastic element having a fine concave-convex structure obtained after treatment with a gas atmosphere of only sulfur hexafluoride (SF6) as shown in Table 3. The dotted line represents the transmittance of the plastic element having a fine concave-convex structure obtained after treatment with a gas atmosphere of only trifluoromethane (CHF3) as shown in Table 3. The double-dashed line represents the transmittance of the plastic element having a fine concave-convex structure obtained after treatment with a gas atmosphere of only oxygen (O2) as shown in Table 3. The thin solid line marked as "unprocessed" represents the transmittance of a plastic element that has not been processed and does not have a fine concave-convex structure.
[0101] according to Fig.15The transmittance of the plastic element with a fine concavo-convex structure obtained after treatment with a gas atmosphere of only trifluoromethane and the transmittance of the plastic element with a fine concavo-convex structure obtained after treatment with a gas atmosphere of only oxygen is approximately the same as the transmittance of the plastic element without a fine concavo-convex structure that has not been treated, and is about 4% to 5% lower than the transmittance of the plastic element with a fine concavo-convex structure obtained by the method of the present invention in the visible light range of 400 nanometers to 700 nanometers. The transmittance of the plastic element with a fine concavo-convex structure obtained after treatment with a gas atmosphere of only sulfur hexafluoride is at most about 1% lower than the transmittance of the plastic element with a fine concavo-convex structure obtained by the method of the present invention in the range below 600 nanometers.
[0102] The above description relates to plastic components made of polycarbonate. The present invention can also be applied to components made of other plastic materials. The following description will be made for the case where the plastic material is acrylic resin.
[0103] Table 4 is a table showing etching conditions of an etching method according to another embodiment of the present invention and the average pitch and average depth of a fine concavo-convex structure generated by the etching method. The plastic component 200 is made of polymethyl methacrylate (PMMA) which is an acrylic resin.
[0104] [Table 4]
[0105]
[0106] Fig.16 This is an SEM image of the antireflection fine concavo-convex structure for visible light produced by the method shown in Table 4.
[0107] Fig.17 It is a graph showing the relationship between wavelength and reflectivity. Fig.17 The horizontal axis represents the wavelength, Fig.17 The vertical axis represents reflectivity. The solid line represents the reflectivity of the plastic element having the fine concavo-convex structure obtained by the method of the present invention shown in Table 4. The dotted line marked as "unprocessed" represents the reflectivity of the plastic element that has not been processed and does not have a fine concavo-convex structure.
[0108] Fig.18 It is a graph showing the relationship between wavelength and transmittance. Fig.18 The horizontal axis represents the wavelength, Fig.18 The vertical axis represents transmittance. The solid line represents the transmittance of the plastic element having the fine concavo-convex structure obtained by the method of the present invention shown in Table 4. The dotted line marked as "unprocessed" represents the transmittance of the plastic element that has not been processed and does not have a fine concavo-convex structure.
[0109] according to Fig.18The transmittance of the plastic element having the fine concave-convex structure obtained by the method of the present invention is above 92% in the visible light range of 400 nm to 700 nm, which is about 3% to 4% higher than the transmittance of the plastic element without the fine concave-convex structure.
[0110] Table 5 is a table showing etching conditions of an etching method according to another embodiment of the present invention and the average pitch and average depth of a fine concavo-convex structure generated by the etching method. The plastic component 200 is made of polymethyl methacrylate (PMMA).
[0111] [Table 5]
[0112]
[0113] In the present embodiment, oxygen is used in the first step and a mixed gas of trifluoromethane and argon is used in the second step to obtain a fine concave-convex structure having a desired average spacing and average depth, which shows that the reactivity of oxygen to polymethyl methacrylate is higher than that of the mixed gas of trifluoromethane and argon to polymethyl methacrylate.
[0114] After the first step in Table 5 was completed, when etching was continued in an oxygen atmosphere, the average depth did not change significantly, the average pitch increased, and the desired average pitch and the desired average depth could not be obtained.
[0115] It is believed that the reason why the fine concavoconvex structure was not generated when etching polycarbonate in an atmosphere containing only oxygen as shown in Table 3 is not because etching was not performed, but because the power and etching time were long, so the entire surface was etched. It is generally believed that the reactivity to plastic materials is in the order of oxygen, sulfur hexafluoride, and trifluoromethane. Carbon tetrafluoride (CF4) can also be used instead of trifluoromethane as a gas with relatively low reactivity to plastic materials.
[0116] The atmosphere gas used in the first step of the etching method of the embodiment of the present invention includes sulfur hexafluoride, a mixture of sulfur hexafluoride and at least one of oxygen or argon, or oxygen. The atmosphere gas used in the second step of the etching method of the embodiment of the present invention includes trifluoromethane, a mixture of trifluoromethane and at least one of oxygen or argon, carbon tetrafluoride, and a mixture of carbon tetrafluoride and at least one of oxygen or argon.
[0117] In the present invention, the average pitch of the fine concavo-convex structure is determined in the first step, and in the second step, the plastic element is treated with an atmospheric gas having a lower reactivity to the plastic element than the atmospheric gas in the first step, thereby increasing the average depth of the fine concavo-convex structure while maintaining the above average pitch. In this way, according to the present invention, a plastic element having a fine concavo-convex structure with a desired pitch and a desired depth can be manufactured.
[0118] The following is a new waterproof treatment method for plastic components with fine concavo-convex structures. In the past, in order to waterproof plastic components with fine concavo-convex structures, the surface of the component was coated with a waterproof film by immersing it in a waterproof coating liquid. However, it is difficult to coat the fine concavo-convex structure on the surface of a lens with a complex shape with a uniform waterproof film. In addition, the treatment requires time and labor, and the waterproof coating liquid is very expensive, so the treatment cost is high.
[0119] In the new waterproofing method, the Figure 1 The reactive ion etching apparatus 100A shown in the figure performs water-repellent treatment on the fine concavo-convex structure on the surface of the plastic component.
[0120] Fig.19 1 is a diagram showing the structure of a waterproofing treatment device 100B used in a waterproofing treatment according to an embodiment of the present invention. The waterproofing treatment device 100B has a reaction chamber 101. Gas is supplied to the vacuum-exhausted reaction chamber 101 from a gas supply port 111. The amount of gas supplied can be adjusted. In addition, a gas exhaust port 113 is provided in the reaction chamber 101, and a valve not shown is installed in the gas exhaust port 113. By operating the valve, the gas pressure in the reaction chamber 101 can be made to a desired pressure value. The reaction chamber 101 is provided with a grounded lower electrode 105 and an upper electrode 103 connected to a high-frequency power supply 107, and plasma can be generated by applying a high-frequency voltage between the two electrodes by the high-frequency power supply 107. A plastic element 200 having a fine concave-convex structure on the surface is arranged on the lower electrode 105. As an example, the plastic element 200 is a lens made of plastic. The lower electrode 105 can be cooled to a desired temperature by a cooling device 109. The cooling device 109 is a device that uses a water-cooled cooler for cooling, for example. The lower electrode 105 is cooled in order to control the reaction by making the temperature of the plastic element 200 a desired temperature.
[0121] Figure 1 The reactive ion etching apparatus 100A shown in FIG. Fig.19 In the waterproofing treatment device 100B shown, only the connection between the high-frequency power supply 107 and the upper and lower electrodes is different. In the waterproofing treatment device 100B, in order to prevent ion-based etching, the lower electrode 105 of the plastic element 200 with a fine concave-convex structure on the surface is grounded. In the waterproofing treatment device 100B, the fluorine free radicals generated by the plasma are combined with the surface of the fine concave-convex structure, thereby implementing waterproofing. The atmospheric gas is selected in a way that the free radicals will not destroy the fine concave-convex structure, and the power of the high-frequency power supply and the processing time are adjusted. It is also possible to use a single device constructed in a way that the connection between the high-frequency power supply and the upper and lower electrodes can be changed to implement etching treatment and waterproofing treatment.
[0122] Table 6 is a table showing water repellent treatment conditions. The plastic component 200 is made of polymethyl methacrylate (PMMA).
[0123] [Table 6]
[0124] Gas pressure Gas Type-Flow RF Power Processing temperature Processing time Condition 1 5Pa CHF3: 50mL / min 100W 10℃ 300sec Condition 2 1Pa CHF3: 50mL / min 50W 10℃ 300sec
[0125] As the atmospheric gas for the water repellent treatment, carbon tetrafluoride or sulfur hexafluoride may be used instead of trifluoromethane.
[0126] Fig. 20 This is a photo of a water droplet formed on the surface of a plastic component with a fine concavo-convex structure that has not been treated for water repellency. In a cross section perpendicular to the surface of the plastic component, the angle formed by the tangent line of the water droplet surface and the surface of the plastic component, i.e. the contact angle, is 38.3 degrees.
[0127] Fig.21 This is a photograph of water droplets formed on the surface of the plastic element having a fine concavo-convex structure subjected to the water repellent treatment according to Condition 1 of Table 6. The contact angle is 139 degrees. The contact angle is significantly increased by the water repellent treatment.
[0128] Fig. 22 This is a photograph of water droplets formed on the surface of the plastic element having a fine concavo-convex structure subjected to the water-repellent treatment according to Condition 2 of Table 6. The contact angle is 137 degrees. The contact angle is significantly increased by the water-repellent treatment.
Claims
1. A method for manufacturing a plastic component having a fine concavo-convex structure on the surface, wherein: In the first step, a micro-concave-convex structure having an average pitch of a specific value ranging from 0.05 micrometers to 1 micrometer is generated on the surface of the plastic component by reactive ion etching in a first gas atmosphere. In the second step, reactive ion etching is performed in a second gas atmosphere to increase the average depth to a value in the range of 0.15 microns to 1.5 microns while approximately maintaining the specific value of the average spacing of the fine concave-convex structure generated in the first step, and the reactivity of the second gas to the plastic element is lower than the reactivity of the first gas to the plastic element.
2. The method for manufacturing a plastic component having a fine concavo-convex structure on the surface according to claim 1, wherein: The first gas is sulfur hexafluoride (SF6), a mixture of sulfur hexafluoride and at least one of oxygen (O2) or argon (Ar), or oxygen.
3. The method for manufacturing a plastic component having a fine concavo-convex structure on the surface according to claim 1, wherein: The gas used in the second step is trifluoromethane (CHF3), a mixture of trifluoromethane and at least one of oxygen or argon, carbon tetrafluoride (CF4), or a mixture of carbon tetrafluoride and at least one of oxygen or argon.
4. The method for manufacturing a plastic element having a fine concave-convex structure on the surface as described in claim 1 further comprises a third step of combining fluorine radicals on the surface of the fine concave-convex structure by plasma treatment in a third gas atmosphere without causing ion etching.
5. The method for manufacturing a plastic component having a fine concavo-convex structure on the surface according to claim 4, wherein: The third gas is trifluoromethane, carbon tetrafluoride or sulfur hexafluoride.
6. The method for manufacturing a plastic component having a fine concavo-convex structure on the surface according to claim 1, wherein: The plastic component is an optical component.
7. The method for manufacturing a plastic component having a fine concavo-convex structure on the surface according to claim 1, wherein: The fine concavo-convex structure is a fine concavo-convex structure for antireflection.
